Mycobacterium avium subsp hominissuis biofilm is composed of distinct phenotypes and influenced by the presence of antimicrobials - McNabe, Molly (2011)
Mycobacterium avium subsp hominissuis, hereafter referred to as M. avium, forms biofilm, a property that, in mice, is associated with lung infection via aerosol. As M. avium might co-inhabit the respiratory tract with other pathogens, treatment of the co-pathogen-associated infections, such as in bronchiectasis, would expose M. avium to therapeutic compounds which may have their origin in other organisms sharing the natural environments. Incubation of M. avium with two compounds produced by environmental organisms, streptomycin and tetracycline in vitro at sub-inhibitory concentrations increased biofilm formation in a number of M. avium strains, although exposure to ampicillin, moxifloxacin, rifampin, and TMP/SMX had no effect on biofilm. No selection of genotypically resistant clones was observed. While bacteria incubation in presence of streptomycin upregulates the expression of biofilm-associated genes, the response to the antibiotics had no association with a regulation of a regulator (LysR) linked to the formation of biofilm in M. avium. Biofilms are made of planktonic and sessile bacteria. While planktonic M. avium is susceptible to clarithromycin and ethambutol (clinically used antimicrobials), sessile bacteria are at least 3- to 4-fold more resistant to antibiotics. The sessile phenotype, though, is reversible, and no selection of resistant clones was observed. Mice infected through the airway with both phenotypes were infected with a similar number of bacteria, demonstrating no phenotype advantage. M. avium biofilm formation is enhanced by commonly used compounds and, in the sessile bacterial phenotype, is resistant to clarithromycin and ethambutol, in a reversible manner.